2022
DOI: 10.1093/cid/ciac758
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic Risk Scores for Prediction of Subclinical Coronary Artery Disease in Persons With Human Immunodeficiency Virus (HIV): The Swiss HIV Cohort Study

Abstract: Background In people living with HIV (PLWH), individual polygenic risk scores (PRSs) are associated with coronary artery disease (CAD) events. Whether PRSs are associated with subclinical CAD is unknown. Methods In Swiss HIV Cohort Study participants of European descent, we defined subclinical CAD as presence of soft, mixed, or high risk plaque (SMHRP) on coronary CT angiography, or as participants in the top tertile of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This is comparable with studies in cohorts without HIV; genome‐wide CAD PRSs with known CVD risk factors in a French‐Canadian cohort of over 11 000 participants yielded C‐statistic of 0.72–0.89 for prevalent CAD, 50 and in the ARIC (Atherosclerosis Risk in Communities) and MESA (Multiethnic Study of Atherosclerosis) cohorts (7237 total participants), yielded C‐statistics of 0.701 and 0.660, respectively. 51 Our results were also comparable with studies in PWH; genome‐wide CAD PRSs in the aforementioned Swiss HIV Cohort Study 48 , 49 yielded a C‐statistic of 0.75 for subclinical CAD plaques using nongenetic risk factors alone, which increased to 0.78 with inclusion of CAD PRSs. 48 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is comparable with studies in cohorts without HIV; genome‐wide CAD PRSs with known CVD risk factors in a French‐Canadian cohort of over 11 000 participants yielded C‐statistic of 0.72–0.89 for prevalent CAD, 50 and in the ARIC (Atherosclerosis Risk in Communities) and MESA (Multiethnic Study of Atherosclerosis) cohorts (7237 total participants), yielded C‐statistics of 0.701 and 0.660, respectively. 51 Our results were also comparable with studies in PWH; genome‐wide CAD PRSs in the aforementioned Swiss HIV Cohort Study 48 , 49 yielded a C‐statistic of 0.75 for subclinical CAD plaques using nongenetic risk factors alone, which increased to 0.78 with inclusion of CAD PRSs. 48 …”
Section: Discussionsupporting
confidence: 83%
“… 47 Another study in 345 PWH from the Swiss HIV cohort study found CAD PRSs to be associated with subclinical CAD presence alone from CCTA but restricted to a cohort of exclusively European ancestry. 48 , 49 To our knowledge, our study is the first to demonstrate that a new multiancestry PRS 26 can reliably predict multiple measures of subclinical CAD, especially high‐risk plaque phenotypes, among PWH from diverse ancestries.…”
Section: Discussionmentioning
confidence: 71%
“…Our finding that TL-PRS was associated with TL decline particularly during untreated HIV infection is interesting, and might suggest that suppressive ART is a strong environmental factor with a larger effect on TL dynamics than genetic background. Because we assessed the TL-PRS in a convenience sample of previously assembled study populations [3,32], our genetic findings should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…First, we analyze TL change pre-ART and on-suppressive-ART in a highly selected population of participants (final n=107). Second, because of limited study population size, we investigated the potential effects of genetic background and of ARVs on longitudinal TL change in 798 additional participants from our previous longitudinal studies [3,32] who had >2 TL measurements available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation